2018
DOI: 10.2217/bmm-2017-0374
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and Tau as Biomarkers of Severity in Multiple Sclerosis

Abstract: BDNF is a good biomarker for diagnosis of MS but not for severity or progression. Tau appears to have a more active role in the progression of MS.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…This reduction was more pronounced in patients with SPMS. These findings at the group level are in line with some previous reports, 5,6,29 while other studies in smaller cohorts 30 did not confirm a difference.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This reduction was more pronounced in patients with SPMS. These findings at the group level are in line with some previous reports, 5,6,29 while other studies in smaller cohorts 30 did not confirm a difference.…”
Section: Discussionsupporting
confidence: 92%
“…3,4 Previous reports have also explored possible links between levels of BDNF in serum and different MS courses. 5,6 In MS lesions, at the cellular level, beyond neurons, BDNF is primarily present in immune cells including T cells and microglial cells, possibly also in reactive astrocytes. 7 A "trophic" interaction between infiltrating immune cells and neurons has been repeatedly discussed [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that brain-derived neurotrophic factor (BDNF) and soluble isoform of the interferon-β (IFN-β) receptor (sIFNAR2) levels may serve as useful biomarkers for the diagnosis of MS [ 20 , 21 ].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The potential biomarkers which can be used to predict the prognosis of relapsed or progressive forms of MS, as well as the responsiveness to treatment in patients with MS are SIRT1 (a NAD-dependent deacetylase sirtuin-1) mRNA, Response gene to complement-32 (RGC-32) , Fasl, IL-21, Tau proteins (proteins that stabilize microtubules), miR-191-5p, miR-128-3p and serum netrin-1 (an axon guidance protein) [ 17 , 21 , 29 , 30 , 31 , 32 ].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%